Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
. Ta có :
\(\dfrac{1}{11}>\dfrac{1}{20}\)
\(\dfrac{1}{12}>\dfrac{1}{20}\)
.................
\(\dfrac{1}{19}>\dfrac{1}{20}\)
\(\dfrac{1}{20}=\dfrac{1}{20}\)
\(\Leftrightarrow\dfrac{1}{11}+\dfrac{1}{12}+......+\dfrac{1}{20}>\dfrac{1}{20}+\dfrac{1}{20}+.....+\dfrac{1}{20}\)
\(\Leftrightarrow S>\dfrac{1}{20}.10\)
\(\Leftrightarrow S>\dfrac{1}{2}\)
2. \(\dfrac{x}{12}=\dfrac{-1}{24}-\dfrac{1}{8}\)
\(\Leftrightarrow\dfrac{x}{12}=-\dfrac{1}{6}\)
\(\Leftrightarrow6x=-12\)
\(\Leftrightarrow x=-2\)
Vậy ...
3. \(\dfrac{2}{5.7}+\dfrac{2}{7.9}+........+\dfrac{2}{19.21}\)
\(=\dfrac{1}{5}-\dfrac{1}{7}+\dfrac{1}{7}-\dfrac{1}{9}+......+\dfrac{1}{19}-\dfrac{1}{21}\)
\(=\dfrac{1}{5}-\dfrac{1}{21}\)
\(=\dfrac{16}{105}\)
\(linh_1=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+\dfrac{1}{3.4.5}\)
\(linh_1=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+\dfrac{1}{3.4}-\dfrac{1}{4.5}\right)\)
\(linh_1=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{4.5}\right)\)
\(linh_1=\dfrac{1}{2}\left(\dfrac{1}{2}-\dfrac{1}{20}\right)=\dfrac{1}{2}.\dfrac{9}{20}=\dfrac{9}{40}\)
\(linh_2=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+\dfrac{1}{3.4.5}+...+\dfrac{1}{8.9.10}\)
\(linh_2=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+\dfrac{1}{3.4}-\dfrac{1}{4.5}+...+\dfrac{1}{8.9}-\dfrac{1}{9.10}\right)\)\(linh_2=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{9.10}\right)\)
\(linh_2=\dfrac{1}{2}\left(\dfrac{1}{2}-\dfrac{1}{90}\right)=\dfrac{1}{2}.\dfrac{22}{45}=\dfrac{11}{45}\)
a/ \(G=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+\dfrac{1}{3.4.5}\)
\(\Leftrightarrow2G=\dfrac{2}{1.2.3}+\dfrac{2}{2.3.4}+\dfrac{2}{3.4.5}\)
\(\Leftrightarrow2G=\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+\dfrac{1}{3.4}-\dfrac{1}{4.5}\)
\(\Leftrightarrow2G=\dfrac{1}{1.2}-\dfrac{1}{4.5}\)
\(\Leftrightarrow2G=\dfrac{1}{2}-\dfrac{1}{20}\)
\(\Leftrightarrow2G=\dfrac{9}{20}\)
\(\Leftrightarrow G=\dfrac{9}{40}\)
b/ \(H=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+.....+\dfrac{1}{8.9.10}\)
\(\Leftrightarrow2H=\dfrac{2}{1.2.3}+\dfrac{2}{3.4.5}+.....+\dfrac{2}{8.9.10}\)
\(\Leftrightarrow2H=\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+.....+\dfrac{1}{8.9}-\dfrac{1}{9.10}\)
\(\Leftrightarrow2H=\dfrac{1}{1.2}-\dfrac{1}{9.10}\)
\(\Leftrightarrow2H=\dfrac{1}{2}-\dfrac{1}{90}\)
\(\Leftrightarrow2H=\dfrac{22}{45}\)
\(\Leftrightarrow H=\dfrac{22}{90}\)
\(a,A=\dfrac{1}{3}+\dfrac{1}{3^2}+\dfrac{1}{3^3}+...+\dfrac{1}{3^{2017}}+\dfrac{1}{2^{2018}}\)
\(3A=1+\dfrac{1}{3}+\dfrac{1}{3^2}+...+\dfrac{1}{3^{2016}}+\dfrac{1}{3^{2017}}\)
\(3A-A=1-\dfrac{1}{3^{2018}}\)
\(A=\dfrac{\left(1-\dfrac{1}{3^{2018}}\right)}{2}\)
\(b,B=1+5+5^2+5^3+...+5^{100}\)
\(5B=5+5^2+5^3+5^4+...+5^{100}+5^{101}\)
\(5B-B=1-5^{101}\)
\(B=\dfrac{\left(1-5^{101}\right)}{4}\)
\(-2\dfrac{1}{4}.\)\(\left(3\dfrac{5}{12}-1\dfrac{2}{9}\right)\)
=\(\dfrac{-9}{4}\).\(\left(\dfrac{41}{12}-\dfrac{11}{9}\right)\)
=\(\dfrac{-9}{4}.\dfrac{41}{12}-\dfrac{-9}{4}.\dfrac{11}{9}\)
=\(\dfrac{-123}{16}-\dfrac{-11}{4}\)
=\(\dfrac{-123}{16}-\dfrac{-44}{16}\)
=\(\dfrac{-79}{16}\)
\(\left(-25\%+0,75+\dfrac{7}{12}\right)\div\left(-2\dfrac{1}{8}\right)\)
=\(\left(\dfrac{-1}{4}+\dfrac{3}{4}+\dfrac{7}{12}\right)\div\left(\dfrac{-17}{8}\right)\)
=\(\left(\dfrac{-3}{12}+\dfrac{9}{12}+\dfrac{7}{12}\right).\dfrac{-8}{17}\)
=\(\dfrac{13}{12}.\dfrac{-8}{17}=\dfrac{-26}{51}\)
a,
\(\left(20+9\dfrac{1}{4}\right):2\dfrac{1}{4}=\left(20+\dfrac{37}{4}\right):\dfrac{9}{4}\\ =\dfrac{117}{4}\cdot\dfrac{4}{9}\\ =\dfrac{117}{9}=13\)
b,
\(\left(6-2\dfrac{4}{5}\right)\cdot3\dfrac{1}{8}-1\dfrac{3}{5}:\dfrac{1}{4}\\ =\left(6-\dfrac{14}{5}\right)\cdot\dfrac{25}{8}-\dfrac{8}{5}\cdot4\\ =\dfrac{16}{5}\cdot\dfrac{25}{8}-\dfrac{32}{5}\\ =10-\dfrac{32}{5}\\ =\dfrac{18}{5}\)
c,
\(\dfrac{32}{15}:\left(-1\dfrac{1}{5}+1\dfrac{1}{3}\right)\\ =\dfrac{32}{5}:\left(-\dfrac{6}{5}+\dfrac{4}{3}\right)\\ =\dfrac{32}{5}:\dfrac{2}{15}\\ =\dfrac{32}{5}\cdot\dfrac{15}{2}\\ =48\)
a, ( 20 + \(9\dfrac{1}{4}\) ) : \(2\dfrac{1}{4}\)
= ( 20 + \(\dfrac{37}{4}\) ) : \(\dfrac{9}{4}\)
= ( \(\dfrac{80}{4}\) + \(\dfrac{37}{4}\) ) . \(\dfrac{4}{9}\)
= \(\dfrac{117}{4}\) . \(\dfrac{4}{9}\)
= \(\dfrac{117}{9}\) = 13
b, ( 6 - \(2\dfrac{4}{5}\) ) . \(3\dfrac{1}{8}\) - \(1\dfrac{3}{5}\) : \(\dfrac{1}{4}\)
= ( 6 - \(\dfrac{14}{5}\) ) . \(\dfrac{25}{8}\) - \(\dfrac{8}{5}\) . 4
= ( \(\dfrac{30}{5}\) - \(\dfrac{14}{5}\) ) . \(\dfrac{25}{8}\) - \(\dfrac{8}{5}\) . 4
= \(\dfrac{16}{5}\) . \(\dfrac{25}{8}\) - \(\dfrac{8}{5}\). 4
= 10 - \(\dfrac{32}{5}\)
= \(\dfrac{50}{5}\) - \(\dfrac{32}{5}\)
= \(\dfrac{18}{5}\)
c, \(\dfrac{32}{15}\) : ( -\(1\dfrac{1}{5}\) + \(1\dfrac{1}{3}\) )
= \(\dfrac{32}{15}\) : ( \(\dfrac{-6}{5}\) + \(\dfrac{4}{3}\) )
= \(\dfrac{32}{15}\) : ( \(\dfrac{-18}{15}\) + \(\dfrac{20}{15}\) )
= \(\dfrac{32}{15}\) : \(\dfrac{2}{15}\)
= \(\dfrac{32}{15}\) . \(\dfrac{15}{2}\)
= 16
B= 1/3+1/4>1/4+1/4=1/2
C= 1/5+1/6+1/7+1/8>1/8+1/8+1/8+1/8=4/8=1/2
D= 1/9+1/10+1/11+...+1/16>1/16+1/16+...+1/16=8/16=1/2
E= 1/17+1/18+...+1/32>1/32+1/32+...1/32=16/32=1/2
vậy A=B+C+D+E>1/2+1/2+1/2+1/2=2
A>2